Progression‐free survival of two cases of high‐risk neuroblastoma with refractory/relapsed disease following surgery alone1. Issue 3 (5th November 2012) - Sokol, Elizabeth; Haut, Paul R.; Gosiengfiao, Yasmin; Feinstein, Kate; Pytel, Peter; Cohn, Susan L.
Abstract Outcome for the vast majority of high‐risk neuroblastoma patients with refractory or relapsed disease is dismal. We report two high‐risk patients who remain progression‐free for more than 113 and 18 months following the diagnosis of refractory/relapsed disease who were treated with surgery alone. Complete resolution of a refractory thoracic mass and relapsed liver nodules was observed in one patient. The refractory/relapsed disease in the second patient has remained stable. In both cases, the tumor showed histologic evidence of neuroblastoma maturation. These cases demonstrate that refractory/relapsed neuroblastoma is clinically heterogeneous and highlight the need for better biomarkers to optimize patient care. Pediatr Blood Cancer 2013; 60: 512–514. © 2012 Wiley Periodicals, Inc.